Primerjava podtestov testa UNB za testiranje uporabe proteze pri otrocih in mladostnikih - Burger, Helena (Rehabilitacija (Ljubljana), 2013)
Background: The aim of our study was to find out whereas subtests of UNB test are of equal difficulty and the results could be comparable between them and whereas the type of prosthesis influenced the final result. Methods: All the tests of all the children and adolescents who visited our outpatient clinic for rehabilitation of children following upper limb amputation and upper limb prosthetics during the year 2012 and the first five months of 2013 were included in the study. All the participants were tested with all the three age-appropriate UNB subtests in a random order. Results: In the youngest two age groups (24 years, 58 years) we did not perform enough tests for valid inference; in the oldest two age groups (9-12 years, 13-21 years) the subtests were found to be of equal difficulty and can thus be considered as mutually comparable. In the oldest age subgroup we observed a ceiling effect for all the subtests for spontaneity of prosthetic use. The most skilled in prosthesis use were adolescents who had a bionic hand; the least skilled were those with a body-powered prosthesis. Conclusion: The UNB test subtests for the 13-21 years age group are mutually comparable; further testing is needed for other age groups.
Keywords: amputacija; Amputation; ocenjevanje izida; outcome measurement; Prostheses and implants; proteze in vsadki; rehabilitacija; Rehabilitation; Upper extremity; vocational rehabilitation; zgornji udi